The "Idea Advantage": How Content Sharing Strategies Impact Engagement in Online Learning Platforms. (February 2022) - Narang, Unnati; Yadav, Manjit S.; Rindfleisch, Aric
In recent years, online learning platforms (e.g., Coursera, edX) have experienced massive growth and have reached nearly 200 million learners. Although their reach is quite large, the impact of these platforms is constrained by a low level of learner engagement. In traditional face-to-face classrooms, educators aim to engage learners by asking them to participate in class discussions and share information about their identity and ideas. However, the effectiveness of these strategies in online learning platforms is uncertain. The authors examine this issue by assessing the impact of two different types of content sharing on learner engagement. The authors conduct a textual analysis of over 12, 000 text postings during an 18-month period (Study 1) and a field experiment among over 2, 000 learners (Study 2) in a popular Coursera offering by a large U.S. university. The results indicate that asking learners to share ideas (vs. their identity) has a stronger effect on their video consumption and assessment completion. The authors explain this "idea advantage" by suggesting that learners who share ideas (vs. identity) exhibit a greater degree of elaboration. This idea advantage is strongest for learners from English-speaking countries and those new to online learning.